The Satisfaction of Russian Tourists on Hotel Service in Bangkok Metropolis - Boonchuay, Krissanabhat; Karnjanakit, Sombat (Academic Journal of Thailand National Sports University, 2022)
This research aimed to study the Russian tourists’ satisfaction of services provided by hotels in Bangkok and to compare the 2 factors affecting the satisfaction, namely, sex and age,. In the data collecting process, questionnaires were the instrument to gather data from sample group of 400 tourists. Afterwards, data was analyzed by SPSS for Windows program employing related statistics which were percentage, frequency, mean, standard deviation, t-test and ANOVA The finding indicate that most Russian tourists were female, aged between 20-40 years old. Russian tourists education were in undergraduated level and had an average monthly income of 20,000-50,000 Rubles. They employed as company employees and made their choices of holiday in Bangkok through magazines/periodicals and the groups were travelled with friends and colleagues. At the time of conducting the questionnaires, they were generally the first time visitation and overall, it could be seen that the average of Russian tourists to Thailand tourism industry was in fair level. Findings of Russian tourists’ satisfaction of services had provided by hotels in Bangkok in 7 different aspects respectively 1. service quality (more satisfactory X = 3.95) 2. accommodation (more satisfactory X = 3.99) 3. facilities in the room (more satisfactory X = 3.84) 4. business services (more satisfactory X = 3.60) 5. cost-effectiveness (more satisfactory X = 3.43) 6. safety and security (more satisfactory X = 3.87) and 7. facilities (more satisfactory X = 3.99) Incomparison of Russian tourists’ satisfaction services provided by hotels in Bangkok, there was significant difference at 0.05 between age group. However there was no significant difference at 0.05 between sex.